Mapping of a new genetic locus responsible for ampicillin resistance in Escherichia coli. - Buchanan, C E (1976)
The ampicillin resistance locus of three different ampicillin-resistant, temperature-sensitive Escherichia coli mutants was mapped between proC and purE and does not correspond to any of the known genes in this region. The mutant gene responsible for the temperature sensitivity and consequent morphological changes in each mutant strain was not located in the same 5-min region, even though the two mutants characteristics co-reverted at a very high frequency.